Growing of the Current of Feminist Theories An Analytical Study - Shahlaa Wali Jabbar (Zanco Journal of Humanity Sciences)
This study is a kind of effort to explore growing the current of different feminist theories in their frame discussions of social differences which women face in society. It tries to explain that, regardless of a given ideology, there are quantities of feminist theories that have been progressed based on developing of society. They can be classified into three main waves depending on their growth from beginning to present. In this study three main perspectives which are (Reform Feminisms)( Resistance Feminisms)( Rebellion Feminisms) distinguished from each other by analyzing the existing feminist theories.